Teaching cartography to blind people: Methodological and technological transformations and perspectives - Ventorini, Sílvia Elena; de Freitas, Maria Isabel Castreghini [UNESP] (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2020)
In this review article it is presented the art state of Tactile Cartography based on its advances and challenges. First, it shows the historical profile at the international and national levels, with an emphasis on publications dating from the 20th and 21st centuries. Afterwards, it discuss on the theoretical and methodological contribution that indicates the propensity to deal with the themes of Geography and Cartography in Education based on research that has Piaget's or Vigotski's theories as its main basis. As research challenges to be faced, there is the standardization of the Tactile Cartographic language, tactile maps production and printing consensus, but mainly, the map teaching methodology for blind students. The final discussions, which guide the contributions indication, are based on experiences with blind students and show the importance of the blind child cartographic initiation from the initiation to drawing, even in the preschool phase, with languages mediation and surrounding environment exploration using their own body as a reference.
O Ensino de cartografia para pessoas cegas: Transformações metodológicas, tecnológicas e perspectivas
Keywords: Drawing; Spacial Representation; Tactile Map